Study of the Physical Properties of Carbonyl Iron Particles-Oriented Magneto-Rheological Elastomer - Seo, J.S.; Kim, M.S.; Yang, K.M.; Lee, J.H.; Chung, K.H. (Asian Journal of Chemistry, 2013)
The physical properties of an anisotropic magneto-rheological elastomer were examined. The magneto-responsible particles were incorporated into a natural rubber matrix at a volume fraction of 0, 10, 20, 30, 40 and 50 vol. %. The magneto-rheological elastomers were prepared using a newly proposed neodymium magnet inserted into the mold to align the particles efficiently. The tensile strength of the anisotropic magneto-rheological elastomer decreased abruptly, whereas the hardness was higher than that of isotropic magneto-rheological elastomer. At an input current of 3A, magneto-rheological elastomer containing 30 vol. % magneto-responsible particle showed the maximum magneto-rheological effect, which was explained by the ratio of the shear modulus of anisotropic magneto-rheological elastomer with that of isotropic magneto-rheological elastomer and the ratio of the shear modulus shift was 59 %. Based on these results, the orientation of magneto-responsible particle can affect the damping properties of magneto-rheological elastomer.